Presentación. Las canonesas del Santo Sepulcro de Zaragoza. Un patrimonio a conservar: Presentation. The canonesses of the Holy Sepulchre of Zaragoza. A heritage to preserve - Ibáñez Fernández, Javier; Tarifa Castilla, María Josefa (Artigrama, 2025)
Presentación. Las canonesas del Santo Sepulcro de Zaragoza. Un patrimonio a conservar